Impact of the Meaningfulness of Life on the Daily Activities of Industrial Workers - Arfian; Harding, Diana; Sulastiana, Marina; Kadiyono, Anissa Lestari (International Journal of Criminology and Sociology, 2022)
Footwear craft is one of the superior products that is distributed in the 3 districts in Bogor Regency. This sector has the potential to absorb labor in order to reduce unemployment and also affect the community’s economy. The aim of this study is to determine the effect of a meaningful life on the work ethic of Muslim footwear craftsmen in Bogor Regency. Samples were taken from 316 craftsmen in 3 districts, namely Ciomas, Tamansari, and Dramaga in Bogor Regency. Quantitative research methods and data analysis techniques using Structural Equation Modeling with Lisrel 8.8 software, was used to test the hypothesis. Furthermore, the Goodness of Fit Index (GFI) value of the Structural Equation Model was 0.92. However, when the calculated GFI value is greater than the critical GFI, it can be considered good and the model suitable. The results showed that the meaning of life affects the Work Ethic of Muslim footwear craftsmen in Bogor Regency